Molecular and microscopical evidence of Ehrlichia spp. and Borrelia burgdorferi sensu lato in patients, animals and ticks in the Czech Republic - Hulinska, D; Votypka, J; Plch, J; Vlcek, E; Valesová, M; Bojar, M; Hulinsky, V; Smetana, K (The new microbiologica, 2002)
We report moderately severe cases of human ehrlichiosis and a lethal one caused by human granulocytic Ehrlichia, the HGE agent, closely related to Ehrlichia phagocytophila and Ehrlichia equi. Their vector is the Ixodes ricinus tick, which also transmits Borrelia burgorferi sensu lato in central, west and east regions of the Czech Republic. The diagnosis was established by PCR with sequence analysis of the genes encoding 16S rRNA of Ehrlichia and with reverse hybridization by using enzyme linked immunosorbent assay with different covalently coupled probes to the activated plate. Ten out of 47 patients and 10 huntsmen were PCR positive and 7 of them seroconverted to the HGE. Coinfection of Ehrlichia phagocytophila with Borrelia burgdorferi sensu lato was detected in 3 patients. Ehrlichia spp., the HGE agent, was isolated and propagated only from one patient in the HL-60 promyelocytic cell line. The maintenance of Ehrlichia in culture and in patients was assayed also by immunocytological staining and electron microscopy. Sequence or hybridization analysis of PCR results in different wild mammals and birds showed significant sources of Ehrlichia fagocytophila in nature. Three variants of E. phagocytophila in wild roe deer and boars, as well as for the first time in birds, have been described. Cultures from the blood of horses, and from the spleen and kidney specimens of roes and boars, PCR positive for Ehrlichia spp., displayed a disappearing level of the pathogen or contamination with other bacteria.
Keywords: Bartonella; Borrelia burgdorferi komplex; Ixodes; Microscopy, Electron; ehrlichióza; lidé; RNA, Ribosomal, 16S; ELISA; RNA ribozomální 16S; Humans; elektronová mikroskopie; Animals; Enzyme-Linked Immunosorbent Assay; Ehrlichiosis; Czech Republic; Sequence Analysis, DNA; zvířata; Ehrlichia; klíště; Česká republika; sekvenční analýza DNA; Borrelia burgdorferi Group